PENGARUH PENGAWASAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR SEKRETARIAT KOMISI PEMILIHAN UMUM KABUPATEN LAHAT - Ervi Sugianti (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this research is to determine the effect of Supervision and Working Environment Against Employee Performance On Election Commission Secretariat Office Lahat regency. Surveillance study variables (X1), Working Environment (X2) on the Performance (Y) either partially or jointly, survey respondents were employees taken as many as 33 respondents. Of the value of the value equation regression equation obtained performance = 5673 + 0107 + 0766 Work Environment Monitoring. Supervision and working environment variables jointly affect the performance with a coefficient of determination of 67.4%. This means that 67.4% of the performance of the general election commission (KPU) Lahat influenced by supervision and work environment, while 32.6% are influenced by other factors outside the model. Partial assay results indicate that monitoring variables no significant effect on performance, while the work environment positive significant effect on performance. This means that the increase in the working environment will also increase the performance of employees of the election commission (KPU) Lahat regency. Thus the hypothesis turns out t value variable working environment for 7,489 bigger than t table. So Ho rejected and accepted Hᵢ. While monitoring the variable has a value of 1.140 t-test, is smaller than t-table, which means accept